A Fixed Point Theorem and Some Generalized Ky Fan's Minimax Inequalities (Communications in Mathematical Research, 2021)
In this paper, we establish a fixed point theorem for set-valued mappingon a topological vector space without "local convexity". And we also establish somegeneralized Ky Fan's minimax inequalities for set-value vector mappings, which arethe generalization of some previous results.